Opening Address at the 7th International Symposium on "Medicine, Humanities, and Media" (The Journal of Medicine, Humanity and Media, 2024)
Yuzhong Ren, Vice President of Peking University, welcomes attendees to the 7th International Symposium on "Medicine, Humanities, and Media". He highlights PKU's pioneering role in Chinese journalism education and recent innovations in health communication, including China's first master's program in this field. Ren emphasizes PKU's commitment to global academic dialogue, evidenced by the symposium's international participation. Focusing on the theme "Resilience-Oriented Health Communication," he underscores its relevance in the context of global health challenges, particularly in the post-pandemic era, and stresses the importance of academic research in guiding this evolving field.